The paradigm nature of today's office : approaches for achieving quality outcomes in AOM / Kadulliah Ghazali, Noorlaila Hj. Yunus and Erne Suzila Kassim - Ghazali, Kadulliah; Hj. Yunus, Noorlaila; Kassim, Erne Suzila (Research Management Institute (RMI), 2008)
In recent years, there has been an increased respect and responsibility given to Administrative Office Managers. In this paper, we seek to explore the most challenging factors encountered by them. strategies pra cticed to minimize the challenges, and the benefits gained. With the globalization, human utilization and information technology advances issues, and the need for the organizations to sustain the growth, the role of Administrative Office Managers becomes even more challenging because of the need to help employees overcome resistance to the new system. A cross-sectional questionnaire survey was then conducted at hospitality organizations in West Malaysia. The findings suggest that regardless ofhotel ranking and the origin of the organization, administrative office managersf ace and adapt similarf actors. There is also a significant relationship between challenges and strategi es, and the ICT investment and deploym ent provide a substantial role in nurturing employees in the organizations. The study is imperative to intensify and enrich the current administrative management and hospital ity management research.